PENGAMBILAN KEPUTUSAN PETANI DALAM BERUSAHATANI LABU SIAM (Sechium edule) (Studi Kasus di Gapoktan Regge Regeneration di Kecamatan Pasirjambu, Kabupaten Bandung) - Hepi Hapsari; Muhamad Rizky Wibowo; Elsha Munziah; Rani Andriani Budi Kusumo; Sri Fatimah (Universitas Galuh, 2023)
Since 2016 there has been a significant shift in farming to chayote commodities in Pasirjambu District, Bandung Regency. Gapoktan Regge Regeneration is a pioneer of chayote farming. The purpose of this study was to determine the factors most considered by farmers in choosing chayote farming and the feasibility of chayote farming. The research method used is qualitative with a case study approach with data collection techniques through interviews, observation, focus group discussions, and a documentation study involving 15 informants selected by the snowball sampling technique. Data were analyzed using AHP (Analytical Hierarchy Process) and RC ratio analysis. The results showed that the most considered factors were economic factors (0,623), followed by social factors and then technical factors in third place. At the criteria level, the profit criteria (0,320) are the criteria that are most considered by farmers to cultivate chayote and after that are the criteria for market availability, farming experience, age, availability of capital, cultivation ability, tools, education level, and availability of seeds at the lowest level. At this time, chayote farming in Pasirjambu District is still profitable and feasible. This can be illustrated by the value of the RC ratio which is greater than 1, the RC ratio is 2,17.